Enhancing personalized learning in engineering education through TUAH digital portfolio: A framework for equitable TVET in Malaysia - Abd Manap, Nurulfajar; Putra, Azma; Abd Halim, Zakiah; Mohd Zain, Anis Suhaila (2024)
The integration of digital technology in Technical and Vocational Education and Training (TVET) is crucial for preparing a skilled workforce aligned with Industry 4.0 demands. This paper introduces the TUAH Digital Portfolio framework, a novel approach to fostering personalized learning and systematically documenting student achievements in engineering education. The framework leverages digital tools to cater to diverse learning preferences and enhance student engagement through the creation and curation of digital portfolios. By utilizing Apple’s ecosystem and native applications, the study developed original digital content for selected engineering courses, incorporating multimedia elements and interactive components. The research involved a mixed-method approach, assessing the impact of the digital portfolios on student performance, motivation, and employability. Findings indicate that the TUAH Digital Portfolio not only supports personalized learning but also provides a comprehensive repository of student competencies, thereby enhancing their visibility and employability. This study underscores the potential of digital portfolios as a transformative tool for equitable TVET education, promoting both academic excellence and workforce readiness in the context of Malaysia’s evolving educational landscape.